The 15-minute community life circle for older people: Walkability measurement based on service accessibility and street-level built environment – A case study of Suzhou, China - Jiang, Zhonghui; Wu, Chunliang; Chung, Hyungchul (Cities, 2025)
The 15-minute community life circle (15-min CLC) concept focuses on providing accessible services for older adults within a short walking distance. However, few studies have developed a comprehensive evaluation system of 15-min CLC walking accessibility for older people, and little is known about the effects of street-level environment characteristics and human perception on 15-min CLC. This study used the Baidu API and an optimized cumulative opportunity method to measure the 5-, 10-, and 15-min CLC walkability for older adults in Suzhou, China. Street-level characteristics and human perception scores, derived from street view semantic segmentation and deep learning, were incorporated into regression models to assess global and local effects on walkability. The results revealed that there was a significant spatial heterogeneity of CLC walkability in Suzhou. The 5- and 10-min CLCs were found lacking in facilities, particularly senior care services. The regression model showed a positive association between perceived safety and CLC walkability, while the proportion of street vegetation negatively affected walkability. The study suggests enhancing senior care, medical, and leisure facilities, especially within 10-min CLCs. Improving service integration in county-level cities and suburbs, and increasing street vegetation in older urban areas, could further enhance the walking environment for older adults. •15-minute community life circles in Suzhou City showed spatial heterogeneity with high-walkability communities clustering in the main urban areas.•The 5- and 10-min CLC failed to provide sufficient facilities for older population, and the senior care facility was significantly lacking.•Human perception of safety showed a positive effect on community life circle walkability, while street vegetation showed basically negative correlation.